2017
DOI: 10.1097/ijg.0000000000000683
|View full text |Cite
|
Sign up to set email alerts
|

Macular Ganglion Cell and Retinal Nerve Fiber Layer Thickness in Children With Refractive Errors—An Optical Coherence Tomography Study

Abstract: This study establishes normative macular GC-IPL and RNFL thickness in children with refractive errors. Our results suggest that high definition optical coherence tomography RNFL parameters and minimum GC-IPL are not affected by AL or myopia in children, and therefore warrants further evaluation in pediatric glaucoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 28 publications
5
19
0
Order By: Relevance
“…Inferior mRNFL and all GCL‐IPL parameters showed no significant correlation with age. As previous authors have reported, no relationship has been found between SE and mRNFL . Consistent with our results, Goh et al found a positive correlation between GCL‐IPL and SE in children, as did Zhao et al in their study with young Chinese people.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Inferior mRNFL and all GCL‐IPL parameters showed no significant correlation with age. As previous authors have reported, no relationship has been found between SE and mRNFL . Consistent with our results, Goh et al found a positive correlation between GCL‐IPL and SE in children, as did Zhao et al in their study with young Chinese people.…”
Section: Discussionsupporting
confidence: 91%
“…As previous authors have reported, no relationship has been found between SE and mRNFL. 8 Consistent with our results, Goh et al 8 found a positive correlation between GCL-IPL and SE in children, as did Zhao et al 29 in their study with young Chinese people. Nevertheless, Jin et al reported no differences in GCL-IPL between refractive groups and a negative correlation with age.…”
Section: Gcl-ipl Totalsupporting
confidence: 92%
See 2 more Smart Citations
“…They were examined with OCT ten or more years after the injury, at an age when age-related loss of ganglion cells is very small. [17][18][19] Fibre tractography of the OR lesions made it possible to localise and estimate the extent of the effect upon the retro-geniculate pathways, allowing for a topographical association Figure 1. Brain injury on MRI, visual field defects and GCL+IPL topography and layer thickness presentation for cases A-F. GW = gestational week, yrs = years, WMDI = white matter damage of immaturity, PCA = posterior cerebral artery, AVM = arteriovenous malformation, OR = optic radiation.…”
Section: Discussionmentioning
confidence: 99%